Utilization of Rhizoctonia Mycorrhizae for Orchid Late Blight Control in Sustainable Agricultural (Biosaintifika: Journal of Biology & Biology Education, 2024)
Vanda tricolor is currently a protected species because is the occurrence of orchid late blight caused by the Fusarium sp. pathogenic fungus. The objective of this study was to investigate the effectiveness of Rhizoctonia mycorrhizae in inducing resistance against Fusarium sp., the causative agent of late blight, in V. tricolor. The research employed CRBD with three treatments and six replications. Rhizoctonia mycorrhizae were isolated and identified following the procedure outlined by Bayman. Pre-inoculation of Rhizoctonia mycorrhizae was conducted on PDA media, and mycorrhizae were subsequently inoculated onto the roots of V. tricolor seedlings derived from tissue culture. The presence of peloton structures on the roots was determined using the Nakano methods. The Saravanan method was employed to measure peroxidase activity. The results demonstrated that V. tricolor induced by Rhizoctonia mycorrhizae exhibited resistance against Fusarium sp. and displayed the formation of peroxidase enzymes, peloton structures, and lignification. In contrast, the non-induced orchids suffered significant damage to the epidermal tissue of the leaves, did not exhibit an increase in peroxidase enzymes, and failed to form peloton or lignified structures. The novelty of this research is the use of Rhizoctonia mycorrhizae to control orchid late blight diseases at Mount Merapi.